Effect of Scarification, Gibberellic acid and Stratification on Seed Germination of Three Pistacia Species - Hassan Abu-Qaoud (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Germinability of P. atlantica Desf., P. palaestina (Bioss) Post. and P. lentiscus L. seeds as influenced by various treatments was investigated. This included four treatments: Acid scarification for 15 minutes, soaking of acid scarified seeds in 1000 ppm GA3 for 24 hours, stratification of seeds at 5Co for 30 days and control (untreated seeds). Significantly, the highest germination (60%) was obtained for P. Palestrina acid scarified plus cold stratified seeds over the control of the three Pistacia species (15, 10, 0%), this percentage (60) was on the same level of significance with the other Pistacia species. Scarifies seeds of P. lentiscus resulted in 13.3% germination, scarified plus GA3 soak of P. lentiscus and P. atlantica Desf. (34, 39.9%), and scarified plus cold stratified P. lentiscus (32%) seeds. Early seed germination was obtained with seeds of P. lentiscus after one week of incubation with scarified plus GA3 (6%) and scarified seeds of P. palaestina (5%), other treated seeds of the three species started germination after two weeks. P. palaestina seeds continued with the highest germination percentage thereafter. Significantly, the longest mean time to complete germination (MTG) was obtained from the control of the three Pistacia species (27.94, 24.50, 30. 04), Scarified P. atlantica (25.84), and scarified plus GA3 soak of P. atlantica (26.25) as compared with the other treatments for the three Pistacia species which were all in the same level of significance.